23.9 W, 985 fs Chirped Pulse Amplification System Based on Yb:YAG Rod Amplifier - Na Na Wang; Xiang Lin Wang; Ting Zhang; Wei Zhang; Xiao Hong Hu; Hao Yuan; Feng Li; Yi Shan Wang; Wei Zhao (IEEE Photonics Journal)
A stable and simple Yb:YAG rod amplifier based on chirped pulse amplification in a water cooling system has been demonstrated. The output power of 38 W at a 250 kHz repetition rate with a spectrum width of 4 nm centered at 1030 nm, which support Fourier-transform limited pulse duration of 389 fs has been generated. The compressed power of 23.9 W with pulse duration of 985 fs has been obtained with a chirped volume Bragg grating compressor. The power stability is measured to be 1.414% when the output power is 35 W. The system is worthwhile to popularize for its good performance and inexpensive cost.